The Effectiveness of Cooperative Learning Model Type Tgt Assisted by Kahoot Application To Improve Students' Cognitive Learning Outcomes Material Pressure Substance Class VIII Middle School - Rosyida, Ummi; Islami, Nur; Azhar, Azhar (Journal of Educational Sciences, 2022)
This study describes the effectiveness of the use of cooperative learning model type TGT (Team Games Tournament) assisted by Kahoot application in improving students' cognitive learning outcomes. The type of research used is quasi-experimental using Posttest Only Nonequvalent Control Group Design. The population of this study was 192 students of class VIII MTs N 1 Meranti Islands. The sample of this research is the students of class VIII A as the control class and the students of class VIII B as the experimental class. The data collection instrument was in the form of a cognitive learning outcome test for class VIII students on substance pressure. Data analysis was carried out by descriptive analysis and inferential analysis using the SPSS version 23 application. The results of this study indicate that there are differences in student cognitive learning outcomes between the control and experimental groups and the use of the TGT type cooperative learning model assisted by the Kahoot application is effectively used to improve students' cognitive learning outcomes. class VIII MTs N 1 Meranti Islands on the subject of Substance Pressure.